Knowledge and Attitude of Menstruation before Menarche among Early Adolescent Girls in Nepal - Timsina, Srijana (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
Every girl experiences menarche in the early adolescent stage of their life. Menarche is the first menstrual period as well as a biological process that is seen with physiological, psychological and emotional change. The knowledge and attitude regarding menstruation and menarche among girls not only determine their reproductive life but are also directly related to the quality of their life. The aim of the research was to assess knowledge about menstruation before menarche and find out restriction’s attitudes during menarche and the menstrual period. In the research, I have selected five secondary schools from Itahari sub-metropolitan city by using convenient sampling and have asked structured questionnaires to 32 early adolescent girls belonging to the Brahmin-Chhetri community to collect primary data. This research finds that 43.75 percent of respondents have low, 41.94 percent have medium and 16.13 percent have high knowledge regarding menstruation before menarche. They receive their first knowledge about menstruation from their mothers. Most respondents think their mothers can give adequate knowledge before experiencing menarche. Likewise, 65-75 percent of respondents are negative towards different kinds of restrictions during menstruation and menarche. The majority 90 percent of respondents agree with the tradition of ‘should not go to the temple and worshipping Gods’ but the practice of restrictions was just opposite from the attitude except worshipping the God and going to the temple. Similarly, the study showed that 56 percent of adolescent girls followed restriction regarding menstruation in order to respect senior members of the family and followed in-home and another 44 percent girls followed it due to the fear of sin. On the basis of the above findings, it is clearly shown that a significant number of mothers of today’s mother generation are not aware of menstruation. They do not give adequate information as knowledge to their daughters and still follow restrictions regarding menstruation as sin, curse, and dirty things.